2006
DOI: 10.1096/fj.05-4749com
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP‐stimulated current in wild‐type and P2X 4 receptor transgenic mouse ventricular myocytes: implications for a cardiac physiologic role of P2X 4 receptors

Abstract: P2X receptors, activated by extracellular ATP, may be important in regulating cardiac function. The objective of the present study was to characterize the electrophysiologic actions of P2X4 receptors in cardiac myocytes and to determine whether they are involved in mediating the effect of extracellular ATP. Membrane currents under voltage clamp were determined in myocytes from both wild-type (WT) and P2X4 receptor-overexpressing transgenic (TG) mice. The P2X agonist 2-meSATP induced an inward current at -100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
58
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 20 publications
(65 reference statements)
9
58
0
Order By: Relevance
“…Ventricular myocytes were obtained from 3-mo-old P2X 4R transgenic (Tg) or wild-type (WT) mice by an enzymatic dissociation procedure as described previously (21,29). The study was approved by the IACUC at the University of Connecticut Health Center.…”
Section: Isolation Of Adult Mouse Cardiac Ventricular Myocytes From P2x4mentioning
confidence: 99%
See 3 more Smart Citations
“…Ventricular myocytes were obtained from 3-mo-old P2X 4R transgenic (Tg) or wild-type (WT) mice by an enzymatic dissociation procedure as described previously (21,29). The study was approved by the IACUC at the University of Connecticut Health Center.…”
Section: Isolation Of Adult Mouse Cardiac Ventricular Myocytes From P2x4mentioning
confidence: 99%
“…Myocyte CS by changes in sarcomere length and Ca 2ϩ transients were recorded simultaneously from single isolated myocytes with an epifluorescence inverted microscope with Ionoptix software and camera (Ionoptix, Milton, MA) as previously described (5,6,10,12). Cells were superfused with Tyrode's solution at 25°C and field stimulated as previously described (21). Ca 2ϩ transients were measured with the ratiometric dye fura 2-AM.…”
Section: Isolation Of Adult Mouse Cardiac Ventricular Myocytes From P2x4mentioning
confidence: 99%
See 2 more Smart Citations
“…13, 14 Recently, the P2X4 receptor (P2X4R) has been reported to control vascular tone and vessel remodeling in at least some blood vessels. [15][16][17][18][19] Interestingly, P2X4R is an important subunit of the native cardiac myocyte P2X receptor, 17 and cardiac-restricted overexpression of P2X4R can induce an enhanced contractile state of the intact heart. 20 More recently, it was found that cardiac overexpression of P2X4R increased cardiac contractility and survival in a model of myocardial infarction-induced cardiac failure.…”
mentioning
confidence: 99%